Situating Poor People in Education Privatization Programs - Lubis, Sofni Indah Arifa (Budapest International Research and Critics University, 2021)
The state-funded schools hold the biggest part in most of countries worldwide. Private-funded schools play a minor role. However, globalization has made the provision of private-funded education gradually increased. Nowadays, the privatization of education is a global phenomenon with all its advantages and disadvantages. Due to this trend a question arise can privatization of education pro-poor people in a more well organized system or optimal way than the state-funded school? Privatization of education policies stand as opposition with the state education policies. Therefore, can the poor people access these private-funded school when the state-funded school is not accessible? Government policies in managing both types of schools are important. Government as the duty bearer of fulfilling the rights to education must ensure that people with all socio-economic background able to access education services.